Plant breeding for water-limited environments - Blum, Abraham (Springer, 2011)
"In general, the book will cater to the needs of plant breeders, researchers/scientists, under-graduate, and graduate students in the field of agriculture. It is a valuable contribution to the current knowledge on  breeding for drought tolerance and provides historical background, successes, and potential for the future. We strongly recommend this book to readers as a valuable source of information and a worthwhile addition to one?s book shelf." - Crop Science Plant breeding for water limited environments has always been a contemporary issue in dryland and rainfed agriculture. However, formal knowledge and methodology in this specific plant breeding domain has been scattered and even lacking, mainly because it is an interdisciplinary endeavor. With the recent looming problem of global warming and water crisis the issue is becoming even more urgent and timely. This book is the first comprehensive and singular treaties on the subject which integrates theory and practice to the extent that it can be used as a plant breeding manual. A main task in writing this book was to sort out the grain from the chaff. In order to achieve it, some threshing was required. The book opens with the essential background on the moisture environment and how it affects plant water status, plant function and plant productivity. It continues from there to explain how plants cope with drought stress by plant constitutive or stress adaptive traits which help to avoid or tolerate dehydration. It concentrates on traits and processes which can be manipulate by plant breeding, separately from those which to date have not yet reached the state of application. Methods of phenotyping and selection for drought resistance are dealt with in detail concentrating again on proven utility, especially under field conditions. Genetic diversity and genetic resources, either practical or potential are discussed and sorted out. Finally, all of the above is funneled into a discussion of some exemplary breeding schemes. The potential of molecular and genomic methods towards breeding for water limited environments are discussed here only where they have been already tested and fully proven as useful at this time. Whereas plant breeding is a science, an engineering project as well as an art, this book is also a reflection of the author?s experience and opinions. It is offered as a sensible and an educational tool to the practitioner, teacher and student in the academia and the industry. Abraham Blum is senior scientist retired from The Volcani Center, Agriculture Research Organization, at Bet Dagan, Israel where he headed the dryland wheat and sorghum breeding programs. Throughout his career his main interest was in understanding how plants cope with drought and heat stress and subsequently identify principles and develop methods for the genetic improvement of plant production under drought and heat stress. He authored numerous scientific papers and reviews on the subject as well as a book entitled ?Plant Breeding for Stress Environments?. Presently he is consulting and teaching, while curating his web site at www.plantstress.com.